Intestinal bacteria-derived tryptamine and its impact on human gut microbiota - Otaru, Nize; Greppi, Anna; Plüss, Serafina; Zünd, Janina; Mujezinovic, Denisa; Baur, Jana; Koleva, Ekaterina; Lacroix, Christophe; Pugin, Benoit (Frontiers in Microbiomes, 2024)
Tryptamine, a neuromodulator derived from tryptophan, has been shown to significantly impact the host gut homeostasis through its production by the gut microbiota. However, the characterization of tryptamine-producing gut bacteria remains limited, the factors regulating tryptamine production largely unexplored, and its effects on the rest of the gut microbial community unknown. In this study, we screened 13 intestinal strains closely related to known tryptamine-producers, characterized their production kinetics, and evaluated whether tryptophan decarboxylation to tryptamine contributes to acid stress tolerance, as shown in other amino acid-dependent acid tolerance systems. We also examined the impact of tryptamine on the composition and function of four healthy human gut microbiota by conducting 48 h ex vivo fecal batch fermentations. To complement ex vivo experiments, we tested the effect of tryptamine exposure (0.5-8 mM range) on the growth of 18 intestinal strains.We identified tryptamine production in five taxa, i.e., Enterocloster asparagiformis, Blautia hansenii, Clostridium nexile, Clostridium sporogenes, and Ruminococcus gnavus, with R. gnavus DSM 108212 accumulating up to 3.4 mM tryptamine after 48 h. Increased tryptophan concentration led to higher tryptamine production. However, tryptamine production was not promoted at low pH, and may not protect cells from acid-induced cellular damage. Exposing gut microbial communities to 2.4 mM tryptamine caused mild changes in gut microbiota function and composition. All donors showed reduced carbohydrate consumption after 5 h, leading to donor-specific alterations of SCFAs (i.e., propionate, acetate, butyrate) and BCFAs (i.e., isobutyrate and isovalerate) after 48 h. Tryptamine also induced mild change of community structure, with a consistent reduction in the phylum Bacteroidota as well as ASVs related to the genera Bacteroides, Blautia, and Faecalibacterium. In vitro, we confirmed the sensitivity of Bacteroides and Faecalibacterium strains at concentrations of 2 mM and above. Multiple gut commensals remained unaffected when exposed to 8 mM tryptamine. Taken together, our findings demonstrated that intestinal bacteria-derived tryptamine is a bioactive molecule that not only alters host homeostasis locally but also modulates the physiology of gut microbial communities. The specific mechanism through which tryptamine exerts its inhibitory effects on specific gut microbes while leaving others unaffected remains to be elucidated.